-6w-8=-4(w+6)

Simple and best practice solution for -6w-8=-4(w+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6w-8=-4(w+6) equation:



-6w-8=-4(w+6)
We move all terms to the left:
-6w-8-(-4(w+6))=0
We calculate terms in parentheses: -(-4(w+6)), so:
-4(w+6)
We multiply parentheses
-4w-24
Back to the equation:
-(-4w-24)
We get rid of parentheses
-6w+4w+24-8=0
We add all the numbers together, and all the variables
-2w+16=0
We move all terms containing w to the left, all other terms to the right
-2w=-16
w=-16/-2
w=+8

See similar equations:

| 2+12x=170 | | d/2+14=17 | | 41+k=-2k+2 | | 70-2y=-9y | | 5x-7=-2(5x-4) | | -26=m-3 | | 3(x+10)=2x+3x-8 | | 5n+5-15×2÷10=2 | | –20+10d=9d | | -15.83-9.9g+14.9g=10g-6.33 | | 1/2(8x+2)= | | 10=x÷6 | | 3c+65=9c-1 | | 3(a+6)-6a=36 | | 5x-7=13+4(x-3) | | 2x-1=8x+4 | | x+8x=5+8x | | 0.14(y-6)+0.20y=0.02y-3 | | 20xx320=930 | | 27+13p=17+14p | | -20+10d=9d | | 7+2t-1=24 | | 180=75+x | | 6+2/3x=x-3 | | 7=7x-4x | | r-9.5=-3.2 | | -7+-3h=-13 | | -3(5h-2)=45 | | 5(u-6)=9u-46 | | 3q=-4+5q | | -3q+8=2 | | j3+ –3=–6 |

Equations solver categories